Optimization of Life Cycle Extension of Asphalt Concrete Mixtures in regard to Material Properties, Structural Design, and Economic Implications - Jan Mikolaj; Lubos Remek; Matus Kozel (Advances in Materials Science and Engineering)
Design of ACM life cycle is defined with respect to traffic load acting on the pavement and road class for a period of about 20 years. In practice, reconstruction is usually pending until the end of the life cycle after which the reconstruction takes place and the original materials are replaced by new materials. Life cycle of the pavement construction in road structure is significantly longer than that of the ACM; it is therefore necessary to consider ACM from a long term viewpoint, that is, exceeding their life expectancy. This paper describes a methodology which consists of analytical calculations, experimental measurements, and optimization of the ACM life cycle with the use of a rehabilitation action to provide new physical properties of pavement surfacing in different periods of the original life cycle. The aim is to attain maximal economic effectiveness, by minimizing financial costs for rehabilitation and maintenance and economic costs of road user. Presented method allows deriving optimal life cycle from various rehabilitation alternatives for particular ACM with the fact that all the necessary parameters are derived from specific experimental measurements and calculations. The method is applicable to all types of ACM materials; however, for each material, it is necessary to carry out the necessary measurements and tests. The article describes the methodology and case study results for a particular type of ACM material.